(untitled) (International Journal of Nursing Education, 2022)
Introduction: The school aged children are going through numerous stressors and anxiety in their life which could impact their academic performance. Yoga is an ancient science that has found useful in enhancing the children’s working memory ability. The main aim of the study to evaluate the effect of MSRT on working memory ability of high school students. Methodology: The Present study consisted of students divided into control group and experiment group. A quasi-experimental research design was used and purposive sampling technique were used to pick a total of 80 samples. Samples who met the inclusion criteria are categorized in to experimental group (n = 40) and Control group (n = 40), Self-structured socio demographic Performa and standardised Digit Span Test used to collect the data in selected High School, Bhubaneswar, Odisha. Result: The study result showed a significant difference between the pre-test and post -test level of working memory after giving the intervention. There was significant association between Working memory ability with the selected demographic variable i.e., Age in year in both intervention and control group. Conclusion: The present study concluded that Mind sound Resonance Technique is effective to enhancing the working memory ability among high school students. Further study can be conducted with large sample and with the alternative technique to improve the working memory ability.